KEPUTUSAN PENDANAAN : PENDEKATAN TRADE-OFF THEORY DAN PECKING ORDER THEORY - MUTAMIMAH MUTAMIMAH; RITA RITA (Jurnal Ekonomi dan Bisnis, 2009)
The purpose of this study is to analyze what Trade-off Theory and Pecking Order Theory ableto explain the financing decision in Indonesian Capital Market. In this study, determinant ofTrade-off theory are non-debt tax shields, size, and liquidity. The determinant of Pecking Ordertheory are profitability, cash deficit, and investment. Sample in this study are 40 manufacturingcompanies that active and liquid at Indonesian capital market over two years, from 2005 to2006. Thus, this study have 80 observations. Sample used the method of purposive sampling.Multiple regression model is used to test this hypothesis. The result of this Trade-off theoryapproach is found that partially all proxy aren’t statistically significant. But simultaniously nondebt tax shields, size, and liquidity variable give statistically significant. While Pecking Ordertheory approach is found that partially only cash deficit and investment variable statisticallysignificant. But simultaneously profitability, cash deficit, and investment variable have statisticallysignificant. So, firms that go public at Indonesian capital market tend to follow peckingorder theory than trade-off theory in their financing decision.Keyword : trade-off theory and pecking order theory